2000
DOI: 10.1021/ef000026b
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Evaluation for Catalytic Biomass Pyrolysis

Abstract: Commercial catalysts, including zeolites (HZSM-5), fluid catalytic cracking (FCC) catalysts, transition metal catalysts (Fe/Cr), and aluminas, were successfully evaluated in a fixed bed catalytic reactor using a mixture of model compounds to simulate biomass flash pyrolysis vapors. Successful criteria including the stability index (SI), the water generation (WG), and the loss of organics (LO) were introduced to monitor the effect of catalysts and ascertain major changes in the obtained liquid product compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 14 publications
11
153
1
2
Order By: Relevance
“…This result is in concordance with the work of Samolada et. al [39], where higher conversions of furfural were obtained during the catalytic pyrolysis of a furfural/organic mixture than when this compound was treated alone. Table 10 shows the CC coke and the amount of C deposited on the catalyst surface (mg C/g catalyst g organic reacted) for the experiments with model compounds.…”
Section: Experimental Steam Reforming Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in concordance with the work of Samolada et. al [39], where higher conversions of furfural were obtained during the catalytic pyrolysis of a furfural/organic mixture than when this compound was treated alone. Table 10 shows the CC coke and the amount of C deposited on the catalyst surface (mg C/g catalyst g organic reacted) for the experiments with model compounds.…”
Section: Experimental Steam Reforming Resultsmentioning
confidence: 99%
“…On the other hand, the reactivity of acetic acid could be different when reforming alone than as part of an organic mixture. Interactions between chemicals in the aqueous fractions might take place during the reforming process, resulting in the formation of different compounds with a different behaviour in the process [39]. In the case of furfural, a lower overall 2 h global conversion was obtained during the reforming of the model compound alone than in the aqueous fraction.…”
Section: Experimental Steam Reforming Resultsmentioning
confidence: 99%
“…Most of the time, the catalysts are supported on alumino-silicate structures, like zeolites [2]. Catalysts can be mixed with the biomass within the reactor [3], or placed in a fixed-bed at the outlet of the pyrolysis reactor [4], or used as a bed material in fluidised bed reactors [5]. Pyrolysis of metal salt impregnated biomass has also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high oxygen (40-50 wt %) and water content (15-30 wt %) and the low H/C ratios, bio-oils cannot be used as transportation fuels directly without prior upgrading. As mentioned earlier additional obstacles are the limited stability of the bio-oils under storage conditions due to the presence of unsaturated compounds and their minor miscibility with conventional liquid fuels (Samolada et al, 2000). Catalytic biomass pyrolysis is a promising approach due to the elimination of costly condensation and re-evaporation procedures prior to bio-oil upgrading (Samolada et al, 2000;Lu et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier additional obstacles are the limited stability of the bio-oils under storage conditions due to the presence of unsaturated compounds and their minor miscibility with conventional liquid fuels (Samolada et al, 2000). Catalytic biomass pyrolysis is a promising approach due to the elimination of costly condensation and re-evaporation procedures prior to bio-oil upgrading (Samolada et al, 2000;Lu et al, 2009a). Several studies have indicated that the viscosity of bio-oil depends on the type of feedstocks, type of pyrolyzer, and pyrolysis conditions.…”
Section: Introductionmentioning
confidence: 99%